Prevalence of blindness in Western Australia: a population study using capture and recapture techniques - Crewe, Julie; Morgan, William; Morlet, Nigel; Clark, Antony; Lam, Geoffrey; Parsons, Richard; Mukhtar, Syed Aqif; Crowley, Margaret; Semmens, James (British Medical Association, 2012)
Aim: To determine the prevalence of blinding eye disease in Western Australia using a capture and recapture methodology. Methods: Three independent lists of residents of Western Australia who were also legally blind were collated during the capture periods in 2008–9. The first list was obtained from the state-wide blind register. A second list comprised patients routinely attending hospital outpatient eye clinics over a 6-month period in 2008. The third list was patients attending ophthalmologists' routine clinical appointments over a 6-week period in 2009. Lists were compared to identify those individuals who were captured on each list and those who were recaptured by subsequent lists. Log-linear models were used to calculate the best fit and estimate the prevalence of blindness in the Western Australian population and extrapolated to a national prevalence of blindness in Australia. Results: 1771 legally blind people were identified on three separate lists. The best estimate of the prevalence of blindness in Western Australia was 3384 (95% CI 2947 to 3983) or 0.15% of the population of 2.25 million. Extrapolating to the national population (21.87 million) gave a prevalence of legal blindness of approximately 32 892 or 0.15%. Conclusion: Capture–recapture techniques can be used to determine the prevalence of blindness in whole populations. The calculated prevalence of blindness suggested that up to 30% of legally blind people may not be receiving available financial support and up to 60% were not accessing rehabilitation services.